Presence of gas in the refluxate enhances reflux perception in non-erosive patients with physiological acid exposure of the oesophagus. Issue 4 (31st August 2007) - Emerenziani, S; Sifrim, D; Habib, F I; Ribolsi, M; Guarino, M P L; Rizzi, M; Caviglia, R; Petitti, T; Cicala, M
Abstract : Objective: The mechanisms underlying symptoms in gastro-oesophageal reflux disease, particularly in non-erosive reflux disease (NERD), remain to be fully elucidated. Weakly acidic reflux and the presence of gas in the refluxate could be relevant in the pathogenesis of symptoms. Methods: To assess the relationship between symptoms and weakly acidic, acid and mixed (liquid–gas) reflux, 24 h oesophageal pH–impedance monitoring was performed in 32 NERD and in 20 oesophagitis patients. In 12 NERD patients the study was repeated following 4 weeks treatment with a proton pump inhibitor (PPI). Impedance–pH data were compared with those of 10 asymptomatic controls. Heartburn and acid regurgitation were considered in the analysis of symptoms. Results: 15 NERD patients showed a physiological acid exposure time (pH-negative). Weakly acidic reflux was significantly less frequent in patients (25% (2%), mean (SE)) than in controls (54% (4%), p<0.01). Gas was present in 45–55% of reflux events in patient groups and controls, and decreased following PPI treatment. In NERD pH-negative patients, weakly acidic reflux accounted for 32% (10%) (vs 22% (6%) in NERD pH-positive and 12% (8%) in oesophagitis patients) and mixed reflux for more than two-thirds of all symptom-related refluxes. Multivariate logistic analysis showed that in NERD pH-negative patients, the risk of reflux perception was significantly higher when gas was present in the refluxate (odds ratio, 3.2; 95% CI, 1.2 to 10; p<0.01). Conclusions: The large majority of symptoms, in all patients, are related to acid reflux. In NERD patients, the presence of gas in the refluxate significantly enhances the probability of reflux perception. These patients are also more sensitive to less acidic reflux than oesophagitis patients.